Combining ability studies for yield and its component traits in safflower (Carthamus tinctorius L.): Combining ability studies for yield and its component traits in safflower (Carthamus tinctorius L.) - P B WADIKAR,; S L DHARE,; S L WAGHMODE, (Journal of Oilseeds Research, 2020)
Combining ability for ten characters was studied by crossing three lines and five testers in line x tester fashion.The estimates of SCA variance were not higher than GCA variance in most of the traits indicating preponderance of non-additive gene action. The line, GMU-2720 had significant positive GCA effects for seed yield/plant, number of branches, number of capitula/plant, number of seed/capitulum, and oil content whereas significant negative GCA effects for days to 50% flowering, days to maturity and plant height. The cross, GMU-2720 x GMU-3423 and JMU1339 x PBN-96 were best for majority of the characters and thus identified as promising cross combinations for further improvement programme in safflower.